2007
DOI: 10.1016/j.cub.2007.09.060
|View full text |Cite
|
Sign up to set email alerts
|

Elephants Classify Human Ethnic Groups by Odor and Garment Color

Abstract: Animals can benefit from classifying predators or other dangers into categories, tailoring their escape strategies to the type and nature of the risk. Studies of alarm vocalizations have revealed various levels of sophistication in classification. In many taxa, reactions to danger are inflexible, but some species can learn the level of threat presented by the local population of a predator or by specific, recognizable individuals. Some species distinguish several species of predator, giving differentiated warn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
79
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(85 citation statements)
references
References 18 publications
5
79
1
Order By: Relevance
“…The Kamba, on the other hand, are agriculturalists with little reason to threaten elephant herds. Previous research has shown that elephants react more negatively to the color and smell of clothing worn by Maasai than that worn by Kamba (11). McComb et al, however, focus here on what is probably the elephants' most acute sensory modality, sound, to assess the elephants' evaluation of human threats.…”
mentioning
confidence: 99%
“…The Kamba, on the other hand, are agriculturalists with little reason to threaten elephant herds. Previous research has shown that elephants react more negatively to the color and smell of clothing worn by Maasai than that worn by Kamba (11). McComb et al, however, focus here on what is probably the elephants' most acute sensory modality, sound, to assess the elephants' evaluation of human threats.…”
mentioning
confidence: 99%
“…African elephants are also already known to make broad distinctions between human ethnic groups on the basis of visual and olfactory cues (15). In the Amboseli ecosystem in Kenya, Maasai pastoralists periodically come into conflict with elephants over access to water and grazing for their cattle, and this sometimes results in elephants being speared, particularly in retaliation when Maasai lives have been lost (15,22). In contrast, Kamba men, with more agricultural lifestyles, do not typically pose a significant threat to elephants within the National Park, and where conflict occurs outside over crop raiding, this largely involves male rather than female elephants (see, for example, ref.…”
mentioning
confidence: 99%
“…This focus has demonstrated that a number of different species are able to use visual cues to distinguish between individual humans that present varying levels of threat (4,5,(14)(15)(16). However, acoustic cues could potentially provide a more effective means of classifying human predators by virtue of enabling categories of particularly dangerous humans to be identified.…”
mentioning
confidence: 99%
“…Elephants did display aggressive behaviours when dangerous Maasai hunter clothes were displayed visually, but Maasai olfactory cues were absent. Bates et al [15] concluded that the presence of clothes without accompanying olfactory cues indicated that the humans were no longer present in the area. Thus, a reduced level of threat perception allowed elephants to react more aggressively, as we propose happened when our elephants perceived lesser threat from leopard growls.…”
Section: Discussionmentioning
confidence: 99%